Relationship between motor skills, participation in leisure activities and quality of life of children with Developmental Coordination Disorder: Temporal aspects. (March 2015) - Raz-Silbiger, S.; Lifshitz, N.; Katz, N.; Steinhart, S.; Cermak, S.A.; Weintraub, N.
Highlights: The study focuses on the relationship between motor skills, leisure participation and quality of life of children with DCD. The relationship between these factors is examined within a temporal context: school days vs. summer vacation. Children's quality of life appears to be related to the leisure-activity level. This relationship seems to differ within the school days and summer vacation. Abstract: The study examined the relationship between motor skills, participation in leisure activities and quality of life (QOL), within a temporal context (school year vs. summer vacation and school days vs. weekends). Parents of 22 children with Developmental Coordination Disorder (DCD) and of 55 typically developing children, aged 6–11, filled out two questionnaires relating to their children's participation in leisure activities (vigorous, moderate and sedentary) and QOL. The Movement Assessment Battery for Children-2 (MABC-2) was administered to their children. Results showed that among the children with DCD, balance scores positively correlated with participation in sedentary activities, and in both groups both balance and aiming and catching were related to the physical and school aspects of QOL. Furthermore, participation in vigorous activities in the summer was positively correlated with social and school QOL. In contrast, among typically developing children, participation in vigorous activities during the school year was negatively correlated with school QOL. Finally, in both groups, participation in sedentary activities during school days was negatively correlated with school QOL. These results suggest that the parents' perceptions of their children's QOL may be related to the level of activeness of the leisure activities but also to temporal aspects. Therefore, it is important that therapists and educators consider the temporal aspects, when consulting with parents and their children regarding participation in leisure activities.